A Damage Model for Corrosion Fatigue Due to Hydrogen Embrittlement - Shi, Yuhao; Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Material Modeling and Structural Mechanics)
Predicting the durability of components subjected to mechanical load under environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. The demand for precise predictions increases with the desire of lightweight design in transportation due to environmental protection. Corrosion with its manifold of mechanisms often occurs together with the production of hydrogen by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions often leading to early and unexpected failure. Until now, predictions are mostly based on costly experiments. Hence, a rational predictive model based on the fundamentals of electrochemistry and damage mechanics has to be developed in order to reduce the costs. In this work, a first model approach based on classical continuum damage mechanics is presented to couple both, the damage induced by the mechanical stress and the hydrogen embrittlement. An elaborated two-scale model based on the selfconsistent theory is applied to describe the mechanical damage due to fatigue. The electrochemical kinetics are elucidated through the Langmuir adsorption isotherm and the diffusion equation to consider the impact of hydrogen embrittlement on the fatigue. The modeling of the mechanism of hydrogen embrittlement defines the progress of damage accumulation due to the electrochemistry. The durability results like the S-N diagram show the influence of hydrogen embrittlement by varying, e.g. the fatigue frequency or the stress ratio.
Keywords: Hydrogen embrittlement; Fatigue; Continuum damage mechanics; Numerical simulation; Multi-field problem

Long-Term Behavior of Clinched Electrical Contacts - Kalich, Jan; Matzke, Marcus; Pfeiffer, Wolfgang; Schlegel, Stephan; Kornhuber, Ludwig; Füssel, Uwe (Metals)
Joining by forming operations presents powerful and complex joining techniques. Clinching is a well-known joining process for use in sheet metalworking. Currently, clinched joints are focusing on mechanically enhanced connections. Additionally, the demand for integrating electrical requirements to transmit electrical currents will be increased in the future. This integration is particularly important, for instance, in the e-mobility sector. It enables connecting battery cells with electrical joints of aluminum and copper. Systematic use of the process-specific advantages of this joining method opens up the possibility to find and create electrically optimized connections. The optimization for the transmission of electrical currents will be demonstrated for clinched joints by adapting the tool geometry and the clinched joint design. Based on a comparison of the electrical joint resistance, the limit use temperature is defined for the joining materials used based on the microstructural condition and the aging condition due to artificial aging. As a result of the investigations carried out, reliable current transmission at a constant conductor temperature of up to 120 °C can be achieved for clinched copper–copper joints. In the case of pure aluminum joints and mixed joints of aluminum and copper, long-term stable current transmission can be ensured up to a conductor temperature of 100 °C.
Keywords: General Materials Science; Metals and Alloys

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Comparison of two mesh-moving techniques for finite element simulations of galvanic corrosion - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Acta Mechanica)
Galvanic corrosion is a destructive process between dissimilar metals. The present paper presents a constructed numerical test case to simulate galvanic corrosion of two dissimilar metals. This test case is used to study the accuracy of different implementations to track the dissolving anode boundary. One technique is to numerically simulate a mesh displacement based on the prescribed displacement at the anode boundary. The second method is to adjust only the boundary elements. Re-meshing after a certain number of time steps is applied to both implementations. They produce similar results for an electrical and electrochemical field problem. This work shows that mesh smoothing does not result in higher accuracy when modeling a moving anode front. Adjusting only the boundary elements is sufficient when frequent re-meshing is used.
Keywords: Mechanical Engineering; Computational Mechanics

Electrical Contacting of Aluminum Bus Bars Using Clinching and Functional Elements - Füssel, Uwe; Schlegel, Stephan; Reschke, Gregor; Kalich, Jan (SFU/ICAFT 2022)
As a joining-by-forming process, clinching and the use of functional elements enable low-energy joining of components through form, force, and, under certain conditions, material closure. In addition to the transmission of mechanical forces, these joining processes can be qualified for additional electrical contact within the scope of functional integration for electro-mobile applications. For this purpose, maximizing the force and material closure is necessary to ensure a long-term, stable transmission of electrical currents. To this end, the electrical properties of the joints were optimized. The investigations carried out show the long-term behavior under normal operating conditions and the short-circuit case.

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Rechnungslegung nach IFRS und HGB: Lehrbuch zur Theorie und Praxis der Unternehmenspublizität mit Beispielen und Übungen - Ruhnke, Klaus; Simons, Dirk; Sievers, Sönke

Asymmetric, non-uniform 3-dB directional coupler with 300-nm bandwidth and a small footprint - Nikbakht, Hamed; Khoshmehr, Mohammad Talebi; van Someren, Bob; Teichrib, Dieter; Hammer, Manfred; Förstner, Jens; Akca, B. Imran (Optics Letters)
Here we demonstrate a new, to the best of our knowledge, type of 3-dB coupler that has an ultra-broadband operational range from 1300 to 1600 nm with low fabrication sensitivity. The overall device size is 800 µm including in/out S-bend waveguides. The coupler is an asymmetric non-uniform directional coupler that consists of two tapered waveguides. One of the coupler arms is shifted by 100 µm in the propagation direction, which results in a more wavelength-insensitive 3-dB response compared to a standard (not shifted) coupler. Moreover, compared to a long adiabatic coupler, we achieved a similar wavelength response at a 16-times-smaller device length. The couplers were fabricated using the silicon nitride platform of Lionix International. We also experimentally demonstrated an optical switch that is made by using two of these couplers in a Mach–Zehnder interferometer configuration. According to experimental results, this optical switch exhibits –10 dB of extinction ratio over the 1500–1600 nm wavelength range. Our results indicate that this new type of coupler holds great promise for various applications, including optical imaging, telecommunications, and reconfigurable photonic processors where compact, fabrication-tolerant, and wavelength-insensitive couplers are essential.
Keywords: tet_topic_waveguide

Separation Of Multi-Component Parts For Mechanical Recycling – Study About Basic Approaches Using A Heating Process - Hopp, Matthias; Schäffer, Leon

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Mit der richtigen Auslegung zur sicheren Verbindung - Moritzer, Elmar; Held, Christian; Hopmann, C.; Kramer, M. (Kunststoffe)

Wie bewährt sich das duale berufliche Ausbildungssystem der industriellen Metall und Elektroausbildung unter Pandemiebedingungen? Lehrkräfte und Auszubildende reflektieren - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s): Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)

Reproducibility and Scattering in Additive Manufacturing: Results from a Round Robin on PBF-LB/M AlSi10Mg Alloy - Schneider, M.; Bettge, D.; Binder, M.; Dollmeier, K.; Dreyer, Malte; Hilgenberg, K.; Klöden, B.; Schlingmann, T.; Schmidt, J. (Practical Metallography)
Abstract The round robin test investigated the reliability users can expect for AlSi10Mg additive manufactured specimens by laser powder bed fusion through examining powder quality, process parameter, microstructure defects, strength and fatigue. Besides for one outlier, expected static material properties could be found. Optical microstructure inspection was beneficial to determine true porosity and porosity types to explain the occurring scatter in properties. Fractographic analyses reveal that the fatigue crack propagation starts at the rough as-built surface for all specimens. Statistical analysis of the scatter in fatigue using statistical derived safety factors concludes that at a stress of 36.87 MPa the fatigue limit of 10 7 cycles could be reached for all specimen with a survival probability of 99.999 %.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Event-Driven Programming of FPGA-accelerated ROS 2 Robotics Applications - Lienen, Christian; Platzner, Marco (2022 25th Euromicro Conference on Digital System Design (DSD))

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (Annales Henri Poincaré)
Abstract The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $$\mathbb {M}$$ M is a stochastic process that models a random perturbation of the geodesic flow. If $$\mathbb {M}$$ M is an orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the $$L^2$$ L 2 -spectrum of the infinitesimal generator of a time-rescaled version of the process converges to the Laplace spectrum of the base manifold.
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Ruelle–Pollicott resonances for manifolds with hyperbolic cusps - Guedes Bonthonneau, Yannick; Weich, Tobias (Journal of the European Mathematical Society)
Keywords: Applied Mathematics; General Mathematics

Soziotechnische Herausforderungen bei der Einführung von RPA managen - Hobscheidt, Daniela; Menzefricke, Jörn Steffen; Gabriel, Stefan; Kühn, Arno; Dumitrescu, Roman (Praxishandbuch Robotic Process Automation (RPA))

The adrenal steroid profile in adolescent depression: a valuable bio-readout? - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hauffa, Berthold P.; Hebebrand, Johannes; Grasemann, Corinna (Translational Psychiatry)
Abstract There is preliminary evidence that adrenal steroids other than cortisol may be valuable biomarkers for major depressive disorder (MDD). So far, studies have been conducted in adults only, and conclusions are limited, mainly due to small sample sizes. Therefore, the present study assessed whether adrenal steroids serve as biomarkers for adolescent MDD. In 261 depressed adolescents (170 females) treated at a single psychiatric hospital, serum adrenal steroids (progesterone, 17-hydroxyprogesterone, 21-deoxycortisol, 11-deoxycortisol, cortisol, cortisone, deoxycorticosterone, corticosterone) were determined by liquid chromatography-tandem mass spectrometry. Findings were compared to that of an age- and sex-matched reference cohort ( N = 255) by nonparametric analysis of variance. Nonparametric receiver operating characteristics (ROC) analyses were conducted to evaluate the diagnostic performance of single steroids and steroid ratios to classify depression status. Sensitivity analyses considered important confounders of adrenal functioning, and ROC results were verified by cross-validation. Compared to the reference cohort, levels of deoxycorticosterone and 21-deoxycortisol were decreased ( P < 0.001). All other glucocorticoid- and mineralocorticoid-related steroids were increased ( P < 0.001). The corticosterone to deoxycorticosterone ratio evidenced excellent classification characteristics, especially in females (AUC: 0.957; sensitivity: 0.902; specificity: 0.891). The adrenal steroid metabolome qualifies as a bio-readout reflecting adolescent MDD by a distinct steroid pattern that indicates dysfunction of the hypothalamus–pituitary–adrenal axis. Moreover, the corticosterone to deoxycorticosterone ratio may prospectively qualify to contribute to precision medicine in psychiatry by identifying those patients who might benefit from antiglucocorticoid treatment or those at risk for recurrence when adrenal dysfunction has not resolved.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. - Caruso, Carina; Neuweg, Georg Hans; Wagner, Michael; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung / Teacher training; Mentoring; Internship; Professionalization; Theory-practice-relation

Inwiefern ist die Professionalisierung in Praxisphasen schulformspezifisch? - Caruso, Carina; Seifert, Andreas (Österreichische Religionspädagogische Forum)
Im Zentrum dieses Beitrags stehen Ergebnisse der Messung pädagogischer Kompetenzen Studierender der Theologie, die das Praxissemester in Deutschland absolviert haben. Das bildungswissenschaftliche Wissen, Kompetenzselbsteinschätzungen und ihre Entwicklung sowie die Einschätzung der im Praxissemester erreichten Ziele Studierender werden dabei unter Berücksichtigung der Ausrichtung des Lehramtsstudiums auf eine Schulform betrachtet. Um die Ergebnisse der Messung bildungswissenschaftlichen Wissens und die der Messung von Kompetenzselbsteinschätzungen zu kontextualisieren (N = 304), wird zuerst die Relevanz des (bildungswissenschaftlichen) Wissens als Ausgangspunkt des Könnens herausgearbeitet. Daran anschließend werden Befunde zur schulformspezifischen Professionalisierung resümiert. Anschließend werden Hypothesen hergeleitet, die Anlage der Studie sowie die Testinstrumente vorge- stellt, die Ergebnisse präsentiert und diskutiert. Die Ergebnisse zeigen wider Erwarten, dass sich weder das bildungswissenschaftliche Wissen, die Kompetenzselbsteinschätzungen und ihre Entwicklung noch die Einschätzung der im Praxissemester erreichten Ziele angehender Lehrkräfte in Abhängigkeit der Schulformen unterscheiden. Die Diskussion bezieht sich u.a. auf die Struktur der Lehramtsstudiengänge, die Denkfiguren zur Entwicklung von Können und die Konzeption der Messinstrumente.
Keywords: Bildungswissenschaftliches Wissen; Kompetenzmessung; Kompetenzselbsteinschätzung; Praxissemester; Professionalisierung / competence measurement; competence self-assessment; educational knowledge; internship; professionalization

Das Belastungserleben von Lehramtsanwärterinnen und -anwärtern im Vorbereitungsdienst - Bruns, Marike; Caruso, Carina; Ackermann, Luisa (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Die Ausbildung von Lehrkräften teilt sich in Studium und Vorbereitungsdienst. Während im Studium Wissen grundgelegt wird, dient der Vorbereitungsdienst, der überwiegend in der Schule stattfindet, dem Erwerb praktischer Kompetenzen, was den Rückbezug auf theoretisch fundierte Kenntnisse und den Aufbau erfahrungsbasierten Wissens umfasst. Die Maßnahmen zur Eindämmung der Corona-Pandemie verändern nicht nur den Schulalltag, sondern haben auch Einfluss auf die Kompetenzentwicklung angehender Lehrkräfte im Vorbereitungsdienst, die ihre Berufsausbildung unter veränderten Rahmenbedingungen durchführen müssen. Die aktuellen Rahmenbedingungen können u. a. aufgrund fehlender bzw. eingeschränkter Praxiserfahrungen eine reguläre Ausbildung erschweren, was zu einem erhöhten Belastungsempfinden der angehenden Lehrkräfte beitragen kann. In diesem Beitrag wird Bezug genommen auf Daten einer explorativen Interviewstudie mit Lehramtsanwärterinnen und -anwärtern aus Nordrhein-Westfalen (N = 19), die während der Pandemie im Jahr 2020 ihren Vorbereitungsdienst absolviert haben. Es wird dabei den Fragen nachgegangen, welche Belastungsfaktoren im Zusammenhang mit der Corona-Pandemie während des Vorbereitungsdienstes auftreten können und inwieweit sich angehende Lehrkräfte während ihres Vorbereitungsdienstes vor dem Hintergrund der aktuellen Rahmenbedingungen infolge der Corona-Pandemie als belastet erleben.
Keywords: Corona-Pandemie; Lehramtsanwärter:innen; Lehrer:innenausbildung; Professionalisierung; Vorbereitungsdienst / corona pandemic; prospective teachers; teacher training; professionalization; preparatory service

Von der Not zur Tugend!? - Caruso, Carina; Bruns, Marike; Harteis, Christian (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s) Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Der Begriff der „Zwangsdigitalisierung“ beschreibt, dass als eine Folge der Corona-Pandemie Präsenzformate durch digital gestützte Settings ersetzt werden sowie Alter- nativen zur Kommunikation und für das gemeinsame Arbeiten und Lernen in Präsenz gefunden werden mussten. Digital gestützte Lehr-Lernsettings scheinen seit dem ersten Lockdown sowohl an Schulen als auch an Hochschulen eine Möglichkeit dafür darzustellen, die Lern- und Entwicklungsprozesse (z. B. von Schülerinnen und Schülern, angehenden Lehrkräften) trotz physischer Distanz weiterzuführen. In diesem Beitrag werden die mit der Zwangsdigitalisierung an den Hochschulen verbundenen Chancen und Grenzen für die Entwicklung digitalisierungsbezogener Kompetenzen angehender Lehrkräfte herausgearbeitet. Dabei richtet sich der Blick auf den Wert von Erfahrungen für Lernen und Entwicklung. Zudem wird, gemäß der den Angebots-Nutzungs-Modellen inhärenten Logik einer „Wirkkette“, Bezug genommen auf Perspektiven von Studierenden, deren prospektiven Schülerinnen und Schülern sowie von Dozierenden.
Keywords: Hochschullehre; Lehrer:innenausbildung; Medienkompetenz / teacher education; teaching at university; media literacy

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for researching professional learning and development: Challenges, applications and empirical illustrations)
Q is an exploratory method used to elicit discrete patterns of subjectivity (e.g., subjective theories, beliefs). To be more concrete, Q method aims to identify homogeneous latent clusters of viewpoints towards a certain topic from a larger more heterogeneous set of (a priori unknown) different viewpoints held by respondents in the population. For this purpose, study participants are asked to sort qualitative statements concerning a certain topic (e.g., their beliefs toward something) into a grid roughly following a normal distribution indicating whether they agree or disagree with the given propositions. This results in a so-called Q-sort for each participant that then can be fed into a factor analysis that compares the different Q-sorts and groups them by similarity. In the first part of the chapter, Q method is introduced. The second part of the chapter describes a small study focusing on student teachers and their perspectives concerning upcoming long-term school internships.
Keywords: Q method; Subjectivity; Internships; Teacher education; Q sort

Zum Ausmaß und Zusammenhang der unterrichtsbezogenen Nutzung digitaler Medien mit der Medienkompetenz von Lehrkräften unter Berücksichtigung von Hintergrundmerkmalen - Caruso, Carina; Heldt, Melanie; Drossel, Kerstin (Lehrerbildung auf dem Prüfstand)

Pädagogische Kompetenz als Ausgangspunkt beruflichen Könnens!? Ergebnisse der Kompetenzmessung angehender Lehrkräfte unter Berücksichtigung individueller Voraussetzungen - Caruso, Carina; Seifert, Andreas (Religionspädagogische Beiträge. Journal for Religion in Education)
Im Zentrum dieses Beitrags stehen Ergebnisse der Messung pädagogischer Kompetenzen Studierender. Dabei werden sowohl das bildungswissenschaftliche Wissen als auch die Entwicklung der Kompetenzselbsteinschätzungen in den Bereichen Unterrichten, Erziehen, Beurteilen und Innovieren unter Berücksichtigung individueller Voraussetzungen (Alter, Geschlecht, Abiturnote, Bachelornote, Konfession) betrachtet. Um die Ergebnisse hinsichtlich ihrer Bedeutung für die Professionalisierung angehender Lehrkräfte diskutieren zu können, wird, den empirischen Erkenntnissen voranstehend, die Bedeutung von Wissen für berufliches Können herausgearbeitet. Daran anschließend werden Hypothesen hergeleitet, die Anlage der Studie sowie die Testinstrumente vorgestellt, die Ergebnisse präsentiert und diskutiert. Die Ergebnisse zeigen, dass die Abitur- und Bachelornote die Varianz hinsichtlich des pädagogischen Wissens aufklären, sich eine signifikante Entwicklung der Kompetenzselbsteinschätzungen angehender Lehrkräfte feststellen lässt, aber sich angehende Religionslehrkräfte kaum von anderen Studierenden unterscheiden. Die Diskussion nimmt u. a. Rückbezug auf die Denkfiguren zur Entwicklung beruflichen Könnens und benennt Limitationen, die mit der Studie und Kompetenzmessungen verbunden sind. Daran schließt die Formulierung eines Ausblicks an. Der Beitrag zielt insbesondere darauf, repräsentative Ergebnisse der Kompetenzmessung zu präsentieren und dabei potenzielle Einflussfaktoren auf die studentische Kompetenzentwicklung zu beleuchten. Ein dadurch angereichertes Konglomerat belastbarer Erkenntnisse zielt darauf, langfristig zur Ableitung lehrerbildungsdidaktischer Überlegungen herangezogen werden zu können, die die studentische Professionalisierung unterstützen.
Keywords: Bildungswissenschaftliches Wissen; Kompetenzmessung; Kompetenzselbsteinschätzung; Praxissemester; Professionalisierung / competence measurement; competence self-assessment; educational knowledge; internship; professionalization

Die Relevanz von Mentor*innen für die Professionalisierung von angehenden Lehrkräften im Praxissemester: Forschungsdesiderate und Handlungsoptionen - Caruso, Carina; Goller, Michael (Die Deutsche Schule)
Im Praxissemester (PS) sind Mentor*innen für Studierende wichtige Bezugspersonen, die sie u.a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im PS mehrere Erkenntnisse vorliegen, ist die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Bericht zielt darauf, die Relevanz von Mentor*innen herauszuarbeiten, Forschungsdesiderate zu umreißen und Handlungsoptionen aufzuzeigen.
Keywords: Mentoring; Praxissemester; Professionalisierung / internships; mentoring; professionalisation

Zur rückblickenden Beurteilung von Fortbildungserfahrungen - Caruso, Carina (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Artikel werden die Relevanz von Lehrer*innenfortbildungen für die Professionalität und Expertise von Lehrkräften beschrieben sowie Forschungsergebnisse zu Lehrer*innenfortbildungen zusammengefasst. Im Zentrum des Beitrags stehen Ergebnisse einer Interviewstudie mit Lehrkräften, die Einblicke in die aktuelle Situation und Praxis von Lehrer*innenfortbildungen aus Sicht von Lehrkräften geben. Dabei werden folgende Fragestellungen aufgegriffen, indem die explorative Studie die Wahrnehmung von Fortbildungsveranstaltungen durch Lehrkräfte erhebt und darstellt: Wie bewerten Lehrkräfte die Rahmenbedingungen externer Lehrer*innenfortbildungen? Was sind aus Sicht von Lehrkräften Aspekte guter bzw. schlechter Fortbildungen? Was wünschen sich Lehrkräfte in Bezug auf die Planung, Gestaltung und Durchführung von Fortbildungen? Nach der Diskussion der Befunde endet der Beitrag mit einem Fazit.
Keywords: Expertise; Lehrerbildung; Professionalisierung; Lehrerfortbildung

Der technische Fortschritt und seine Implikationen aus pädagogischer Perspektive - Caruso, Carina; Martin, Alexander (Digitalisierungsbezogene Kompetenzen fördern: Herausforderungen, Ansätze und Entwicklungsfelder im Kontext von Schule und Hochschule)
Technologien beeinflussen verschiedene Bereiche des menschlichen Lebens. Gegenwärtig kommt insbesondere digitalen Technologien ein hoher Stellenwert zu, der sich u. a. dadurch auszeichnet, dass die Nutzung digitaler Technologien sowohl den privaten bzw. informellen als auch den beruflichen bzw. formellen Lebensraum betrifft. Diese Omnipräsenz digitaler Technologien im menschlichen Alltag macht digitalisierungsbezogene Kompetenzen zu einer Voraussetzung für eine selbstbestimmte gesellschaftliche Teilhabe und ist somit auch eine zentrale Zielperspektive schulischer Bildungs- und Erziehungsprozesse. Lehrkräfte, die Schüler*innen auf das Arbeiten und Leben in einer digital vernetzten Welt vorbereiten sollen, stehen deshalb vor einer doppelten Herausforderung: einerseits – wie jeder Mensch – sich selbst angesichts der Digitalisierung zurecht zu finden und entsprechende Medienkompetenzen auszubilden und andererseits medienpädagogische und digitalisierungsbezogene Kompetenzen zu entwickeln, um Lerngelegenheiten für den Unterricht konzipieren und bereitstellen zu können, die Schüler*innen den Erwerb von Medienkompetenzen ermöglichen. Die Lehrer*innenbildung in Deutschland umfasst drei Phasen: Studium, Vorbereitungsdienst und Fort- und Weiterbildung. Digitalisierungsbezogene Kompetenzen sollen angehende Lehrkräfte schon im Studium erwerben und in den anschließenden Phasen weiterentwickeln. In diesem Beitrag werden zunächst Merkmale einer digital vernetzten Welt als Ausgangs- und Bezugsunkte für Lern- und Bildungsprozesse beschrieben (Kap. 2). Daran anschließend werden Kompetenzbereiche erläutert, denen auf dieser Grundlage ein hoher Stellenwert zukommt (Kap. 3). Nach der Herleitung der Forschungsfrage (Kap. 4) und der Beschreibung der Methode (Kap. 5) werden exemplarische Ergebnisse einer Inhaltsanalyse von Studienordnungen nordrhein-westfälischer Lehramtsstudiengänge dargestellt (Kap. 6) und diskutiert (Kap. 7). Die Ergebnisse der Analyse der Studienordnungen der Fächer Katholische Theologie bzw. Unterrichtsfach Pädagogik zeigen, dass angehenden Lehrkräften zum Teil curricular verankerte Lerngelegenheiten fehlen, um in der ersten Phase der Lehrer*innenbildung digitalisierungsbezogene Kompetenzen zu erwerben.

L_2 error estimates for polynomial discrete penalized least-squares approximation on the sphere from noisy data - Hesse, Kerstin; Le Gia, Quoc Thong (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics

Die Vielseitigkeit von Beschichtungen im Spritzgießwerkzeug- und Formenbau - Moritzer, Elmar; Rauen, Dennis; Schilp, Catharina; Scholle, Maximilian (Zeitschrift Kunststofftechnik)

Situation-specific Development of Business Models within Software Ecosystems - Gottschalk, Sebastian
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a challenging activity. On the one hand, various tasks of business model development methods (BMDMs) need to be performed. On the other hand, different decisions for the business models (BMs) need to be made. Both have to fit the changeable situation of the organization in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, the BMDMs and the BMs must be developed situation-specific. In this thesis, we conduct a design science research study to design a novel approach for the situation-specific development of business models with three stages. In the first stage, we create a method repository with method fragments for the BMDMs and a canvas model repository with modeling fragments for the BMs. Both repositories are filled by the knowledge of domain experts. Out of these repositories, in the second stage, situation-specific BMDMs for developing situation-specific BMs are composed by a method engineer based on the changeable situation of the organization and enacted by a business developer. The business developer collaborates with other stakeholders during the enaction to create artifacts. Moreover, in the third stage, he receives IT support, provided by development support engineers, in different development steps.

Qualifizierung mechanischer Fügeverfahren für Batteriekästen - Han, Daxin; Meschut, Gerson

Seizing the Opportunity for Automation—How Traffic Density Determines Truck Drivers' Use of Cruise Control - Hoffmann, Christin; Thommes, Kirsten (IEEE Transactions on Human-Machine Systems)
Keywords: Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Signal Processing; Control and Systems Engineering; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Germany - Schönhärl, Korinna; Osterloh-Konrad, Christine (History and taxation. The dialectical relationship between taxation and the political balance of power: 2021 EATLP Congress Antwerp, 3-4 June 2021)

Interpunktion - Tophinke, Doris (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Orthographie - Tophinke, Doris (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

"Hätten Sie kurz Zeit für mich?" Den Konjunktiv gebrauchen (Basisartikel) - Tophinke, Doris (Praxis Deutsch)

Reactive Direct Bonding of Digital Light Process Components - Moritzer, Elmar; Driediger, Christine (Macromolecular Symposia)

Verfahrenserweiterung des Widerstandselementschweißens für stahlintensive Dreiblech-Hybrid-Mischverbindungen mit zwei höchstfesten Stahlgüten in Mittel- und Basislage - Haak, Viktor; Meschut, Gerson (12. Fügetechnisches Gemeinschaftskolloquium)

Konjunktiv gebrauchen

Emotionale Erfahrungen von Lehramtsstudierenden bei der Arbeit mit Eigenvideografien von Unterricht – Fallanalysen aus einer längsschnittlichen Interviewstudie im Praxissemester - Pollmeier, Pascal; Rogge, Tim; Vogelsang, Christoph (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Arbeit mit Videografien eigenen Unterrichts wird in Praxisphasen in der universitären Lehramtsausbildung zunehmend als methodisches Mittel zur Reflexion von Unterrichtserfahrungen genutzt. Als wesentlicher Einflussfaktor für einen erfolgreichen Einsatz werden dabei die begleitenden Emotionen der Studierenden angenommen. In einer längsschnittlichen Interviewstudie wurden daher die emotionalen Prozesse von 20 Lehramtsstudierenden bei der Arbeit mit Eigenvideografien in Begleitveranstaltungen des Praxissemesters untersucht. Dabei konnten drei Typen rekonstruiert werden, die prototypische emotionale Muster im Praxissemesterverlauf beschreiben, die durch die Valenz emotionaler Zustände bezüglich der Eigenvideografie zu Beginn und Ende des Praxissemesters charakterisiert werden können (negativ-positiv, positiv-positiv, negativ-negativ). Bei fallübergreifender Betrachtung konnten zudem zentrale Zusammenhänge zwischen Emotionen und Merkmalen des Videoeinsatzes identifiziert werden, wie die Vertrautheit mit Mitstudierenden, der Prozess der Aufnahmegenehmigung und Vorerfahrungen mit Eigenvideografie. Die Ergebnisse der Studie können zur Vermeidung intensiver negativer Emotionen bei der Nutzung videobasierter Reflexion eigenen Unterrichts beitragen und die Akzeptanz von Eigenvideografie zur eigenen Professionalisierung in der Lehrerbildung erhöhen.

Effects of school closures during the COVID-19 pandemic in early 2020 on prospective teachers in a one-semester school internship - Vogelsang, Christoph; Wiethoff, Christoph (European Journal of Teacher Education)
Keywords: Education

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education